2023
DOI: 10.3390/min13030324
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Sugar Mill Waste Ash as Pozzolanic Material in Structural Mortar

Abstract: Bagasse is produced as a waste in the sugar production process, which is used as fuel to stoke boilers in the sugar mills. The concluding product of this burning is residual sugarcane bagasse ash (BA), which is normally dumped or used as low-quality fertilizer. The ash for this study was collected from a reputed sugar mill located in the northern region of Bangladesh. Type I Portland cement (PC) was partially replaced with that finely ground bagasse ash without any pretreatment. The ground BA was used as a rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
(97 reference statements)
0
2
0
Order By: Relevance
“…These periods also decreased by 20% and 14.6% for CEMA10, respectively, compared with those for CEMA0. This observation contradicts the inherent properties of pozzolanic materials, which suggests a delay in the setting time as the cement percentage diminishes [7]. It is suggested that the high fineness and silica content of SCSA provided a suitable condition to make the 10% (w/w) replacement ratio not a critical point in delaying the reactions between cement and water.…”
Section: Blaine Value and Setting Timementioning
confidence: 91%
See 1 more Smart Citation
“…These periods also decreased by 20% and 14.6% for CEMA10, respectively, compared with those for CEMA0. This observation contradicts the inherent properties of pozzolanic materials, which suggests a delay in the setting time as the cement percentage diminishes [7]. It is suggested that the high fineness and silica content of SCSA provided a suitable condition to make the 10% (w/w) replacement ratio not a critical point in delaying the reactions between cement and water.…”
Section: Blaine Value and Setting Timementioning
confidence: 91%
“…The ashes of various agricultural wastes, such as sugarcane bagasse [5,6] date palm [5], wheat straw [6], and corn husk, have been utilized as supplementary cementitious materials (SCMs). The term "Agro-cement" is used to describe the mixing of ash-based agricultural residues with cement, which is the main constituent of concrete [7]. This hypothesis is based on the ability of agro-waste ash to acquire higher proportions of amorphous silica, further maintaining a pozzolanic interaction with Ca(OH) 2 , i.e., Ca [8].…”
Section: Introductionmentioning
confidence: 99%